Analisis Literasi Teknologi Informasi dan Komunikasi (TIK) Aparatur Sipil Negara Pemerintah Kabupaten Minahasa Tenggara - Andi, Fitria; Karouw, Stanley D.S.; Punuhsingon, Charles Punuhsingon S.C. (Jurnal Teknik Informatika, 2020)
Abstract - ICT has developed rapidly and needs to be mastered in this era, which is needed by everyone. Especially for the government, which in this case is the State Civil Apparatus as a performance support. Knowledge of ICT literacy is one important factor to support government performance. But in reality there are still many weaknesses found in ICT literacy in the State Civil Apparatus. The title of this study is "Analysis of ICT Literacy in the State Civil Apparatus at the Government of Southeast Minahasa Regency" which is a study conducted based on the problems as we have mentioned above. The results of this study found that ICT literacy in the State Civil Apparatus at the Government of Southeast Minahasa Regency is classified as moderate or quite capable, although it is still low in network management. Data found from the results of this study can be used as evaluation material for the Government of Southeast Minahasa Regency to support the implementation of e-government and improve public services in Southeast Minahasa and to support the preparation of a master plan for Southeast Minahasa Regency.Keywords: ICT Literacy, Southeast Minahasa, State Civil ApparatusÂ Abstrak - TIK menjadi sesuatu yang berkembang pesat dan mutlak untuk dikuasai di era sekarang ini yang dibutuhkan semua kalangan masyarakat. Terutama bagi pemerintah dalam hal ini Aparatur Sipil Negara sebagai penunjang kinerja. Untuk menunjang kinerja maka pengetahuan literasi TIK merupakan salah satu faktor yang penting. Namun pada kenyataannya literasi TIK pada ASN masih banyak dijumpai kelemahan. Dengan adanya permasalahan tersebut maka dilakukan penelitian dengan judul Analisis Literasi TIK Aparatur Sipil Negara Pemerintah Kabupaten Minahasa Tenggara.Dari penelitian tersebut didapati bahwa Literasi TIK pada ASN Pemerintah Kabupaten Minahasa Tenggara sudah tergolong menengah atau cukup mampu namun termasuk tingkatan yang rendah dalam pengelolaan jaringan. Data yang ditemukan dari hasil penelitian dapat digunakan sebagai bahan evaluasi Pemerintah Kabupaten Minahasa Tenggara guna mendukung terlaksananya e-pemerintahan dan peningkatan layanan publik di Minahasa Tenggara dan untuk menunjang penyusunan rencana induk Kabupaten Minahasa Tenggara.Kata kunci : ASN, Literasi TIK, Minahasa Tenggara